Morphological Changes In The Spleen During The Polypragmation Of 5 Different Types Of Anti-Inflammatory Medicines In Album Rats (American Journal of Pediatric Medicine and Health Sciences (2993-2149), 2023)
The following morphological changes occurred in the spleen under the influence of 5 different types of anti-inflammatory drugs in 3-month-old white purebred rats: fullness in the red pulp vessels, especially in the venous vessels, edema in the vessel wall in the small arterial blood vessels of the spleen, uneven inner surface of the vessel. and small thromboses were detected, intravascular and intratissue hemosiderosis, interstitial edema, an increase in damaged and fragmented blood-shaped elements, especially at the expense of erythrocytes, an increase in the amount of macrophages and lymphocytes in the red pulp was observed.